Performance evaluation of high capacity mechanised dehusking equipment for green arecanut (Areca catechu L.) - Naik, Ravindra; Sadvatha, R.H.; Senthilkumar, T.; Balaji, V. (Journal of Plantation Crops, 2020)
India is a major arecanut (Areca catechu L.) growing country. Of the many problems identified in arecanut processing, dehusking is found to be a major one, which is cumbersome and needs to be mechanised. Presently, there are a few types of equipments available, but these machines are basically of low capacity and cater to small arecanut growers. Performance evaluation of three high capacity green arecanut dehusking equipments was taken up, to work out its possible adoption for entrepreneurship development. Equipment under evaluation consisted of power mounted dehusker with hook tooth cutting blade fixed in a cutting wheel to dehusk the outer shell with a nut ejection system coupled with a vibrating deck of trays to grade and convey the dehusked nuts. The Blade-Knurl shaft speed ratio was optimised as 1:11. Whole nut recovery per cent ranged from 81.84 ± 1.87 to 82.52 ± 1.95 per cent. The unhusked per cent and partially husked percentage ranged from 7.60 ± 3.71 to 7.81 ± 4.68 and 8.29 ± 2.15 to 8.85 ± 2.82, respectively. The broken nut percentage ranged from 1.03 ± 1.36 to 2.06 ± 2.72 percentage. The total cost of operation for two-belt, four-belt and six-belt model was ` 162 h-1,` 237 h-1 and ` 262 h-1, respectively. Better dehusking efficiency with reduced damage to the nuts achieved in mechanical dehusking would enable the farmer to realise additional yield with saving in time and lower cost of operation.